Estereotipos negativos que influyen en la violencia física y psicológica contra el adulto mayor en el asentamiento humano albujar y manuel guarniz del distrito de guadalupe, durante el año 2013 - Llanos Ygnacio, Carmendina (2013)
The study was carried out was how negative stereotypes affect the physical and psychological violence against the Elderly? This was developed through a simple of 217 families (each family is composed of at least 3 and up to 5) Human Settlement Albujar and Manuel Guarniz, using the inductive-deductive, ethnographic and statistical methods, as well as techniques of direct observation, interview and survey methods. Discrimination by the family, is perceived by the elderly as a fact that always develops mostly (64.9%), although the family did not recognize it that way, mostly because for them, this situation occurs only sometimes (39.2%), this situation is caused by negative stereotypes that influence physical and psychological violence against the elderly, identifying themselves as follows: Impaired memory and mental abilities in the elderly, irritability and moodiness of the elderly, loss of interest activities for older adults, older adults lose the ability to solve problems, defects are exacerbated with age, older adults do not do a good job and are unproductive, the view of older adults is not important. Regarding the devaluation of the elderly, most of the elderly family does not listen or give them importance, psychologically and physically abusing situation generated by negative stereotypes about the thought that older people lose their ability to solve problems.